Long-term surgical outcomes of bile duct tumor thrombus versus portal vein tumor thrombus for hepatocellular carcinoma: a propensity score matching analysis - Li, Yi-Nan; Wei, Shao-Ming; Fu, Yang-Kai; Zeng, Zhen-Xin; Huang, Li-Ming; Lv, Jia-Hui; Chen, Wei-Zhao; Wei, Yong-Gang; Zhang, Zhi-Bo; Zhou, Jian-Yin; Wu, Jia-Yi; Yan, Mao-Lin (Frontiers in Oncology, 2024)
Background Portal vein tumor thrombus (PVTT) seriously affects the prognosis of hepatocellular carcinoma (HCC). However, whether bile duct tumor thrombus (BDTT) significantly affects the prognosis of HCC as much as PVTT remains unclear. We aimed to compare the long-term surgical outcomes of HCC with macroscopic PVTT (macro-PVTT) and macroscopic BDTT (macro-BDTT). Methods The data of HCC patients with macro-BDTT or macro-PVTT who underwent hemihepatectomy were retrospectively reviewed. A propensity score matching (PSM) analysis was performed to reduce the baseline imbalance. The recurrence-free survival (RFS) and overall survival (OS) rates were compared between the cohorts. Results Before PSM, the PVTT group had worse RFS and OS rates than the BDTT group (P = 0.043 and P = 0.008, respectively). Multivariate analyses identified PVTT (hazard ratio [HR] = 1.835, P = 0.016) and large HCC (HR = 1.553, P = 0.039) as independent risk factors for poor OS and RFS, respectively. After PSM, the PVTT group had worse RFS and OS rates than the BDTT group (P = 0.037 and P = 0.004, respectively). The 3- and 5-year OS rates were significantly higher in the BDTT group (59.5% and 52.1%, respectively) than in the PVTT group (33.3% and 20.2%, respectively). Conclusion Aggressive hemihepatectomy provides an acceptable prognosis for HCC patients with macro-BDTT. Furthermore, the long-term surgical outcomes of HCC patients with macro-BDTT were significantly better than those of HCC patients with macro-PVTT.